Methadone does not potentiate the effect of doxorubicin in canine tumour cell lines. Issue 3 (19th April 2020) - Cueni, Claudia; Nytko, Katarzyna J.; Thumser‐Henner, Pauline; Weyland, Mathias S.; Rohrer Bley, Carla
Abstract: Opioid receptor activation was shown to enhance the efficacy of anti‐neoplastic drugs in several human cancer cell lines. In these cell lines, doxorubicin increased the number of opioid receptors and methadone concurrently enhanced cellular doxorubicin uptake. Triggered through lay press and media, animal owners started to challenge veterinary oncologists with questions about methadone use in anti‐cancer therapy. Especially in veterinary medicine, where side effects of chemotherapy are tolerated to a lesser extent and hence smaller doses are given, agents potentiating chemotherapeutic agents would be an optimal approach to treatment. Canine transitional cell carcinoma cells (TCC, K9TCC), canine osteosarcoma cells (OSA, Abrams) and canine hemangiosarcoma cells (HSA, DAL‐4) were incubated with different combinations of methadone, buprenorphine and doxorubicin, in order to test inhibition of cell proliferation. Opioid receptor density was assessed with fluorescence‐activated cell sorting in drug native and doxorubicin pretreated cells. In TCC and OSA cell lines opioid receptor density increased after doxorubicin pretreatment. In combination treatment, however, we did not find significant potentiation of doxorubicin's inhibitory effect on proliferation in these cell lines. Neither was there a significant increase of the effect of doxorubicin when the opioids were added 24 hr before doxorubicin. Hence, we could not confirm the hypothesis that opioids increase the anti‐proliferative effect of the anti‐neoplastic drug doxorubicin in any of these canine tumour cell lines. The lack of effect on a cellular level does not warrant a clinical approach to use opioids together with doxorubicin in dogs with cancer. Abstract : Triggered through lay press and media, animal owners started to challenge veterinary oncologists with questions about methadone use in anti‐cancer therapy. However, we could not confirm the hypothesis that opioids increase the anti‐proliferative effect of the anti‐neoplastic drug doxorubicin in any of these canine tumor cell lines. The lack of effect on a cellular level does not warrant a clinical approach to use opioids together with doxorubicin in dogs with cancer.